Women's education in India present status perspective plan,statistical, indicators with global view - Agrawal, S P; Sherwani, M W K (Assist.); Yasin, Madhavi (Assist) (New Delhi Concept, 2001)
The special feature of this publication is the global view of the women's education and the full integration of women in society on equal terms with men and empowering them. This book also presents the Declaration and the platform for Action as adopted in
Keywords: Women-Education; Feminism; Educationl statistics; Women; Child development